Problems and Prospects in the Applying Methods of Analysis Educational Data (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
At the present stage, education is the most important component of the development of a country's economic growth. Often a changing situation requires high professionalism and considerable intellectual effort to make an effective decision. The increase in information flows and the analysis of relevant information generated by the participants in the educational process plays an important role in the process of quality management of the education process. The creation of training systems and the spread of network technology has led to the accumulation of a large amount of data, and this has in turn aroused great interest in the study of Data Mining methods used to analyze the new type of educational data. In this paper, a comparison of methods for analyzing educational data (EDM) and learning analytics (LA) was made, and attention to their peculiarities was paid.As a practical implementation, the behavior of a time series is proposed, which describes the number of studies in 4 scientific fields Azerbaijan for the period from 2014 to 2019, and a short-term forecast is presented.